Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.7150/jca.57711
|View full text |Cite
|
Sign up to set email alerts
|

Trop2 binding IGF2R induces gefitinib resistance in NSCLC by remodeling the tumor microenvironment

Abstract: Gefitinib has shown good efficacy in treating recurrent or advanced non-small cell lung cancer (NSCLC), but the drug resistance remains a clinical challenge in medical oncology. In addition, the complex interaction between tumor cells and heterogeneous stromal cells in the adjacent tumor microenvironment (TME) is also an important contributor to drug resistance. So, it is very necessary to detect the related target genes before and after gefitinib treatment dynamically. In this study, the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In non-small cell lung cancer (NSCLC) cells, treatment with cisplatin induced TROP2 expression accompanied by chemoresistance due to an upregulation of the MAPK signaling pathway [ 33 ]. Moreover, EGFR-mutated NSCLC cells with high TROP2 expression developed more rapid resistance to gefitinib therapy through the interaction of TROP2 with insulin-like growth factor 2 receptor (IGF2R), the induction of AKT, and the remodeling of the tumor microenvironment [ 34 ]. The latter observation is probably related to the fact that TROP2 expression in cancer cells is a predictor of a response to treatment with AKT inhibitors [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…In non-small cell lung cancer (NSCLC) cells, treatment with cisplatin induced TROP2 expression accompanied by chemoresistance due to an upregulation of the MAPK signaling pathway [ 33 ]. Moreover, EGFR-mutated NSCLC cells with high TROP2 expression developed more rapid resistance to gefitinib therapy through the interaction of TROP2 with insulin-like growth factor 2 receptor (IGF2R), the induction of AKT, and the remodeling of the tumor microenvironment [ 34 ]. The latter observation is probably related to the fact that TROP2 expression in cancer cells is a predictor of a response to treatment with AKT inhibitors [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The insulin-like growth factor 2 receptor (IGF2R) was found to be located in the MET nanoenvironment, and co-IP demonstrated the indirect interaction between IGF2R and MET (Figure S11). IGF2R contributes to tumor angiogenesis and drug resistance; it is an unfavorable prognostic protein marker. The correlation between IGF2R and MET provides a new perspective for the study of IGF2R in promoting tumor mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al. reported that Trop2 binding to IGF2R upregulated the IGF2-IGF1R-Akt axis to enhance resistance to gefitinib and remodeling of the tumor microenvironment in NSCLC ( 21 ). In our study, a significant correlation was observed between IGF2R expression and the stromal score, indicating a potential regulatory effect of IGF2R on the tumor microenvironment and LSCC progression.…”
Section: Discussionmentioning
confidence: 99%